New Low-Cost Automated Processing of Digital Photos for Documentation and Visualisation of the Cultural Heritage - Karel Pavelka; Jan Řezníček (Geoinformatics FCE CTU, 2011)
The 3D scanning is nowadays a commonly used and fast technique. A variety of type’s 3D scanners is available, with different precision and aim of using. From normal user´s point of view, all the instruments are very expensive and need special software for processing the measured data. Also transportation of 3D scanners – poses a problem, because duty or special taxes for transport out of the EU have to be paid and there is a risk of damage to dismantling of these very expensive instruments and calibration will be needed. For this reason, a simple and automated technique using close range photogrammetry documentation is very important. This paper describes our experience with the software solution for automatic image correlation techniques and their utilization in close range photogrammetry and historical objects documentation. Non-photogrammetrical approach, which often gives very good outputs, is described the last part of this contribution. An image correlation proceeds well only on appropriate parts of documented objects and depends on the number of images, their overlapping and configuration, radiometrical quality of photos, and surface texture.